The 3′ UTRs of Brain-Derived Neurotrophic Factor Transcripts Differentially Regulate the Dendritic Arbor - O’Neill, Kate M.; Donohue, Katherine E.; Omelchenko, Anton; Firestein, Bonnie L. (Frontiers in Cellular Neuroscience, 2018)
The patterning of dendrites is regulated by many factors, such as brain-derived neurotrophic factor (BDNF), which our laboratory has previously shown alters the dendritic arbor uniquely depending on the mode of extracellular application. In the current work, we examine how BDNF affects dendritogenesis in hippocampal neurons when it is overexpressed intracellularly by transcripts previously reported to be transported to distinct cellular compartments. The BDNF gene is processed at two different polyadenylation sites, leading to mRNA transcription with two different length 3’ untranslated regions (UTRs), and therefore, different mRNA localization preferences. We found that overexpression of BDNF mRNA with or without 3’ UTRs significantly alters dendritic branching compared to branching in control neurons as analyzed by Sholl distribution curves. Unexpectedly, we found that the overexpression of the shorter BDNF mRNA (reported to be preferentially targeted to the cell body) results in similar changes to Sholl curves compared to overexpression of the longer BDNF mRNA (reported to be preferentially targeted to both the cell body and dendrites). We also investigated whether the BDNF receptor TrkB mediates these changes and found that inhibiting TrkB blocks increases in Sholl curves, although at different distances depending on the transcript’s UTR. Finally, although it is not found in nature, we also examined the effects of overexpressing BDNF mRNA with the unique portion of the longer 3’ UTR since it was previously shown to be necessary for dendritic targeting of mRNA. We found that its overexpression increases Sholl curves at distances close to the cell body and that these changes also depend on TrkB activity. This work illustrates how the mRNA spatial code affects how BDNF alters local dendritogenesis and how TrkB may mediate these effects. Finally, our findings emphasize the importance of intracellular transport of BDNF mRNAs in the regulation of dendrite morphology.